All We Need is Love and a Really Soft Pillow! - Reynolds, Peter H. 1961- (Peter Hamilton); Reynolds, Henry Rocket (New York : Orchard Books, an imprint of Scholastic Inc., 2023)
Poppy believes that all they need in life is love, but the Little One keeps coming up with other things that will make their life comfortable--until it is all swept away in a storm.
Keywords: Love -- Juvenile fiction; Families -- Juvenile fiction; Personal belongings -- Juvenile fiction; Storms -- Juvenile fiction; Love -- Fiction; Family life -- Fiction; Personal belongings -- Fiction; Storms -- Fiction; Picture books; JUVENILE FICTION / Family / General (see also headings under Social Themes); JUVENILE FICTION / Social Themes / Poverty & Homelessness; Picture books